Resistance againts spinosad in Plutella xylostella linnaeus (diamondback moth) and its cross resistance to other insecticides - Mohd Ishadi, Nur Adibah (2020)
Plutella xylostella (Diamondback moth, DBM) has developed resistance to different classes of insecticides over the years in Malaysia. This study aimed at establishing the resistance development and mechanism of DBM towards spinosad resistance. The parameters assessed were the role of specific enzymes (P450, GST and esterases), the fitness cost in resistant strain, mode of resistance inheritance, resistance stability and cross resistance potential with other selected insecticides. DBM was obtained from Ladybird Organic Farm, Selangor. Bioassay conducted on spinosad-selected (Spi-Sel) from parent (P) generation to the 15th generation (G15) showed approximately 42.81- fold increase in the resistance. P450 had significantly 4-fold higher activity (p<0.05) in the Spi-Sel strain than in susceptible (SS) strain. Spi-Sel strain experienced high fitness cost during resistance development (relative fitness: 0.25). The larva of SS strain had significantly higher survival rate while larva of Spi-Sel strain required significantly shorter time to complete the stage. Spinosad resistance in Spi-Sel strain was governed by a single major autosomal factor that was inherited recessively. The recessiveness of the resistance was represented by the value of degree of dominance (DLC) of F1 and F1’, -0.6062 and 0.0311 respectively. The overlapping fiducial limit between the F1 and F1’ concluding the autosomal inheritance. No significant deviation (P>0.05) between the expected and observed mortality of the backcross (BC2) population implied monofactorial resistance. Spinosad-decaying (Spi-Dec) strain was produced by terminating the selection at G27 to study the resistance stability. The LC50 ranging from 547.33 to 132.57 ppm from G1 until G5 implying the unstable resistance. Moderate cross resistance was recorded towards emamectin and deltamethrin (RR = 3.8 and RR = 3.49, respectively) and low cross resistance recorded towards chlorantraniliprole (RR = 1.16). Unstable resistance accompanied by moderate to low cross resistance to other insecticides in the present finding suggested that resistance to spinosad in DBM can be reversed to susceptible status again and that resistance can be delayed by alternating the spinosad with insecticides of different classes and mode of action.